2020
DOI: 10.1016/j.jvs.2020.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Physical Distancing, Face Masks, and Eye Protection to Prevent Person-to-Person Transmission of SARS-CoV-2 and COVID-19: A Systematic Review and Meta-Analysis

Abstract: Study design: Systematic review and meta-analysis of 21 standard World Health Organization-specific and COVID-19-specific sources through May 3, 2020.Key findings: In a review of 25,697 patients, transmission of viruses was lower with physical distancing of 1 meter or more compared with less than 1 meter. Protection was increased as distance was lengthened (absolute risk, 3% with longer distance vs 13% with shorter distance). Face mask use could result in a large reduction in risk of interaction (adjusted risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
1,581
6
102

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,361 publications
(1,737 citation statements)
references
References 0 publications
48
1,581
6
102
Order By: Relevance
“…Population movement between regions is an important factor influencing the spread of epidemics [15], while virus testing along with case isolation and community quarantine has been proved to be able to prevent rapid local outbreak [16]. Physical distancing of 1 m or more and wearing masks are also believed to significantly reduce the risk of virus transmission [17]. In addition, the government's promotion of positive preventive measures can contribute to the inhibition of the outbreak [18].…”
Section: Discussionmentioning
confidence: 99%
“…Population movement between regions is an important factor influencing the spread of epidemics [15], while virus testing along with case isolation and community quarantine has been proved to be able to prevent rapid local outbreak [16]. Physical distancing of 1 m or more and wearing masks are also believed to significantly reduce the risk of virus transmission [17]. In addition, the government's promotion of positive preventive measures can contribute to the inhibition of the outbreak [18].…”
Section: Discussionmentioning
confidence: 99%
“…There is epidemiological evidence that masks reduce infection, even when imperfect (118,119). Any face covering will catch large droplets from a cough or sneeze (120), but aerosol particles follow the airflow and escape through any gaps at the edges (19).…”
Section: Implications For Mask Designmentioning
confidence: 99%
“…The main reasons for these discrepancies were the limited evidence on their efficacy in preventing respiratory infections during epidemics; the need to preserve limited supplies of face masks for professional use in healthcare settings; the argument that face masks may create a false sense of security and lead to neglecting other important measures such as hand hygiene and social distancing, and that people may not wear them properly or repeatedly touch their mask, causing more harm than good (26,27). Recent research has shown that face masks could reduce the transmission of the virus (28,29), resulting in many governments advising or mandating the use of masks for healthy individuals in the community. However, there are still debates on the potential risks of wearing masks, such as unintended negative consequences and the effectiveness of different face coverings (30,31).…”
Section: Case Study: Wearing Face-coveringsmentioning
confidence: 99%